Performance factors related to the different tennis backhand groundstrokes: A review - Genevois, C.; Reid, M.; .Rogowski, I.; Crespo, M (Journal of Sports Science & Medicine, 2015)
The backhand is one of the two basic groundstrokes in tennis and can be played both with one or two hands, with topspin or backspin. Despite its variety of derivatives, the scientific litera-ture describing the backhand groundstroke production has not been reviewed as extensively as with the serve and the forehand. The purpose of this article is to review the research describing the mechanics of one and two-handed backhands, with a critical focus on its application to clinicians and coaches. One hundred and thirty four articles satisfied a key word search (tennis, back-hand) in relevant databases and manual search, with only 61 of those articles considered directly relevant to our review. The consensus of this research supports major differences between both the one- and two-handed strokes, chiefly about their re-spective contributions of trunk rotation and the role of the non-dominant upper extremity. Two-handed backhand strokes rely more on trunk rotation for the generation of racquet velocity, while the one-handed backhands utilize segmental rotations of the upper limb to develop comparable racquet speeds. There remains considerable scope for future research to examine ex-pertise, age and/or gender-related kinematic differences to strengthen the practitioner`s understanding of the key mechani-cal considerations that may shape the development of proficient backhand strokes.